Samodzielność decyzyjna spółki zależnej w grupie kapitałowej = Decision-making independence of a subsidiary in a capital group - Sobotkiewicz, Dariusz (Zielona Góra: Oficyna Wydawnicza Uniwersytetu Zielonogórskiego)
The chapter presents the issue of self-determination of internal business entities in a multientity organization. Particular attention and a lot of space was devoted to the issue of decision-making independence in different types of multi-entity organizations (capital groups), taking into account the role of the parent entity in shaping the freedom of action of subordinate units, which are at different stages of development in the host country. Determinants affecting increasing and decreasing the scope of subsidiaries` autonomy are indicated and discussed.
Keywords: jednostka nadrzędna; spółka zależna; samodzielność decyzyjna; parent company; subsidiary; decision-making autonomy